Profiling Hand Hygiene Adherence in an Outpatient Clinic Setting - Nur Inayah Rauf; Asrar As (Global Health Practice Journal, 2025)
Infection prevention and control (IPC) represents a critical priority in healthcare delivery, with hand hygiene serving as a key quality indicator. This study aimed to profile hand hygiene compliance at Clinic X in Makassar City. A descriptive cross-sectional study was conducted involving 32 healthcare staff, including clinicians, allied health professionals, and support staff, selected through total sampling. Data collection employed direct observation using a standardised checklist based on the WHO "Five Moments" framework and the six-step hand hygiene technique. The overall hand hygiene compliance rate was 96.05%. Moment-specific analysis revealed perfect compliance (100%) after contact with patients, body fluids, and patient surroundings. However, compliance before patient/specimen contact was 91.5%, and notably, no hand hygiene opportunities were observed before aseptic procedures during the study period. Alcohol-based hand rubs were the predominant method (84.47%) compared to handwashing with soap (15.53%). Despite exemplary overall compliance supported by a robust safety culture, significant vulnerabilities persist in procedural infection prevention. The disparity between reactive and proactive hand hygiene underscores the need for targeted interventions, particularly through enhanced clinical auditing before aseptic procedures. Further investigation into the behavioural determinants underlying these compliance gaps is strongly recommended.